Employment Determination with Variable Productivity - William A. Jackson (British Review of Economic Issues, 1990)
A macroeconomic model can depict employment only if it includes an account of the organisation of production. Keynes and many Keynesian writers have retained a neoclassical view of production, with fixed, technically efficient production functions; such a view is restrictive and neglects the social aspects of organising production. The present paper sets up a simple post-Keynesian model in which employment and productivity are allowed to be fully variable. To close the model an explicit representation of the organisation of production must be added, and the neoclassical view is only one possibility among others. Several alternatives are considered, as well as policies aimed at reorganising production. It is argued that post-Keynesian economics should rest on a non-neoclassical view of production, acknowledging the scope for variable productivity.
Keywords: B50; E12; E23; E24; O33; 330; employment; productivity; Keynesian economics; organisation of production; technical change